(untitled) (Journal on Excellence in College Teaching, 2024)
This mixed-methods study examined end-of-semester evaluations from an undergraduate course comparing perceptions of instructional support, academic support, and instructor caring in online and face-to-face settings. Results showed statistically significant differences in perceptions of instructional support, with lower ratings in online sections. Qualitative analyses revealed that students emphasized aspects of caring and support, depending on the course context. Differences highlight that while students may have lower ratings of instructional support in online courses, with careful planning and preparation, it is possible to provide caring, supportive environments in the online context.